Ni bioavailability in oat (Avena sativa) grown in naturally aged, Ni refinery-impacted agricultural soils. Issue 6 (18th August 2019) - Gopalapillai, Yamini; Dan, Tereza; Hale, Beverley
ABSTRACT: Risk assessments now use a tiered approach, beginning with conservative methods and moving toward site-specific or bioavailability-based methods, to understand the true risk posed by a contaminant. We examine four different estimates of bioavailable Ni that aim to describe oat ( Avena sativa ) toxicity: (1) total Ni in soil, (2) environmentally available Ni fraction (oxalate extractable), (3) environmentally bioavailable Ni fraction (free ion activity in pore water), and (4) toxicologically bioavailable Ni fraction (metal concentration in plant tissue). We tested three different agricultural soil types (sand, till clay, and heavy clay) from Port Colborne (Ontario, Canada) that naturally aged for decades after receiving aerial Ni deposition from the local Ni refining operations. Nickel rarely occurs in isolation of other elements and so field-based effects data are relatively rare. Port Colborne offers a unique opportunity to assess effects of Ni from a common anthropogenic source. Validation of bioavailability-based predictive models indicated that the Tissue Residue Approach (TRA) best predicted observed oat toxicity, while the Terrestrial Biotic Ligand Model (TBLM) and the Free Ion Activity Model (FIAM) fared better than the Total Metal Model (TMM). Our field-based study supports findings of laboratory-based studies which suggest that toxicity expressed as total Ni in soil can be improved upon.